Comparative assessment of daily curves in patients with cataract associated with pseudoexfoliation syndrome (PEX) before and after phacoemulsification with IOL implantation - M. Z. Frankovska-Gierlak; B. E. Malyugin; V. S. Chubar; A. N. Bessarabov (Офтальмохирургия, 2020)
Purpose. To perform a comparative analysis of the 24-hour control of intraocular pressure (IOP) amplitudes in patients with complicated cataract associated with PEX before and after phacoemulsification of cataract.Material and methods. The clinical study was carried out in 154 eyes of 154 patients with cataract associated with pseudoexfoliation syndrome (PEX). All patients diagnosed with cataract associated with PEX were divided into 3 groups: the group 1 included patients with normal IOP level preoperatively (n=55); the group 2 included patients with IOP ophthalmohypertension preoperatively (n=57); the group 3 included patients with primary open-angle initial glaucoma (n=42). The study of the amplitude of 24-hour fluctuations of IOP and diurnal curve of IOP before and after cataract phacoemulsification was performed. Before the PHACO+IOL the amplitude of diurnal IOP fluctuations was in the group 1: 5.22±0.49 mm Hg, and in the groups 2 and 3: 6.81±1.21 mmHg and 6.60±1.49 mm Hg, respectively.Results. Patients of the group 1 had a significant decrease in the amplitude of diurnal IOP fluctuations by 1.27±0.93 mm Hg (p<0.001). A decrease in the amplitude of diurnal IOP fluctuations by 2.34±1.26 mm Hg (p<0.001) was noted in patients of the group 2. In the group 3 a decrease in the amplitude of diurnal IOP fluctuations by 1.15±1.14 mm Hg (p<0.001) was observed. A tendency of changes in diurnal IOP curves after surgery was revealed in all cases.Conclusion. PHACO+IOL in patients with cataract associated with PEX allows to normalize the level, amplitude and type of diurnal IOP curve.